'Cod Liver Oil': The Art and Criticism of Cordelia Oliver. Issue 1 (2nd January 2020) - Thompson, Susannah
Abstract : The artist, critic and curator Cordelia Oliver was an incisive and highly respected art critic in Scotland from the late 1950s to her death in 2009. Through her critical writing and curatorial practice, she offered a unique perspective on the production and reception of art from Scotland in the mid-to-late twentieth century. This paper focuses particularly on Oliver's role as an artist-critic and her efforts to ensure the visibility and critical reputation of painting by women in Scotland, including many of her peers and contemporaries such as Bet Low, Margot Sandeman and Joan Eardley, and later painters, including Carole Gibbons and Pat Douthwaite.